Monopoly quality degradation in cable television - Gregory S. Crawford; Matthew Shum (The Johns Hopkins University, Department of Economics, 2003)
Using an empirical framework derived from models of nonlinear pricing, we estimate the degree of quality degradation in cable television markets. We find lower bounds on quality degradation ranging from 11% to 45% of observed service qualities. Furthermore, cable operators in markets with local regulatory oversight tend to offer significantly higher quality products, and engage in less quality degradation. While prices are also higher in markets with local regulatory oversight, we find that consumers experienced greater quality per dollar in these markets compared to consumers in markets without regulatory oversight.
Keywords: L12; L50; L43; D42; 330; Kabelfernsehen; Dienstleistungsqualität; Monopol; USA